On the stability of L4,5 in the perturbed relativistic R3BP with a triaxial bigger primary - Nakone, Bello; Singh, Jagadish (International Journal of Advanced Astronomy, 2016)
In the present paper, we endeavor to study the stability of triangular points under the influence of small perturbations in the Coriolis and centrifugal forces, together with the triaxiality of the bigger primary in the framework of the relativistic R3BP. It is observed that the locations of these points are affected by the relativistic factor, triaxiality and a small perturbation in the centrifugal force, but are unaffected by that of the Coriolis force. It is also seen that for these points the range of stability region increases or decreases according as equation (14) without is greater or less than zero.